Multipotent stromal cells induce human regulatory T cells through a novel pathway involving skewing of monocytes toward anti‐inflammatory macrophages. (4th October 2013) - Melief, Sara M.; Schrama, Ellen; Brugman, Martijn H.; Tiemessen, Machteld M.; Hoogduijn, Martin J.; Fibbe, Willem E.; Roelofs, Helene
ABSTRACT Multipotent stromal cells (MSC) have been shown to possess immunomodulatory capacities and are therefore explored as a novel cellular therapy. One of the mechanisms through which MSC modulate immune responses is by the promotion of regulatory T cell (Treg) formation. In this study, we focused on the cellular interactions and secreted factors that are essential in this process. Using an in vitro culture system, we showed that culture‐expanded bone marrow‐derived MSC promote the generation of CD4+CD25hiFoxP3+ T cells in human PBMC populations and that these populations are functionally suppressive. Similar results were obtained with MSC‐conditioned medium, indicating that this process is dependent on soluble factors secreted by the MSC. Antibody neutralization studies showed that TGF‐β1 mediates induction of Tregs. TGF‐β1 is constitutively secreted by MSC, suggesting that the MSC‐induced generation of Tregs by TGF‐β1 was independent of the interaction between MSC and PBMC. Monocyte‐depletion studies showed that monocytes are indispensable for MSC‐induced Treg formation. MSC promote the survival of monocytes and induce differentiation toward macrophage type 2 cells that express CD206 and CD163 and secrete high levels of IL‐10 and CCL‐18, which is mediated by as yet unidentified MSC‐derived soluble factors. CCL18 proved to be responsible for the observed Treg induction. These data indicate that MSC promote the generation of Tregs. Both the direct pathway through the constitutive production of TGF‐β1 and the indirect novel pathway involving the differentiation of monocytes toward CCL18 producing type 2 macrophages are essential for the generation of Tregs induced by MSC. Stem Cells2013;31:1980‐1991